Cardiac hematological malignancies: typical growth patterns, imaging features, and clinical outcome - Voigt, Peter; Weber, Marc-André (Angiology, 2018)
Cardiac hematological malignancies (CHMs) are rare entities and comprise lymphoma, leukemic infiltration, and extramedullary manifestation of multiple myeloma. The aim of this work is to summarize typical growth patterns, imaging features, and outcome parameters of CHM. Overall, 12 cases from 4 centers were reviewed retrospectively together with 604 cases from the literature. Cardiac hematological malignancies were mainly represented by B-cell lymphoma (70.0%). Other entities were rarer. Almost half of the patients showed involvement of multiple cardiac structures. Most commonly right atrium, right ventricle, pericardium, left atrium, and left ventricle were affected in decreased order of frequency. Cardiac hematological malignancies manifested with 3 growth patterns: intracaval masses, heart wall infiltration, and pericardial effusion. Several subtypes of CHM tended to present with different patterns. Clinical presentation is unspecific—frequent signs were dyspnea (54.6%), arrhythmias (30.5%), and thoracic pain (18.5%). Outcome of CHM is poor with mean survival of 283.6 days for leukemias, 260.1 days for T-cell non-Hodgkin lymphoma (NHL), 217.9 days for B-cell NHL, and 155.5 days for multiple myeloma.